Five-Year Outcome of Catheter Ablation of Persistent Atrial Fibrillation Using Termination of Atrial Fibrillation as a Procedural Endpoint. (February 2015) - Scherr, Daniel; Khairy, Paul; Miyazaki, Shinsuke; Aurillac-Lavignolle, Valerie; Pascale, Patrizio; Wilton, Stephen B.; Ramoul, Khaled; Komatsu, Yuki; Roten, Laurent; Jadidi, Amir; Linton, Nick; Pedersen, Michala; et al.
Abstract : Background—: This study aimed to determine 5-year efficacy of catheter ablation for persistent atrial fibrillation (AF) using AF termination as a procedural end point. Methods and Results—: One hundred fifty patients (57±10 years) underwent persistent AF ablation using a stepwise ablation approach (pulmonary vein isolation, electrogram-guided, and linear ablation) with the desired procedural end point being AF termination. Repeat ablation was performed for recurrent AF or atrial tachycardia. AF was terminated by ablation in 120 patients (80%). Arrhythmia-free survival rates after a single procedure were 35.3%±3.9%, 28.0%±3.7%, and 16.8%±3.2% at 1, 2, and 5 years, respectively. Arrhythmia-free survival rates after the last procedure (mean 2.1±1.0 procedures) were 89.7%±2.5%, 79.8%±3.4%, and 62.9%±4.5%, at 1, 2, and 5 years, respectively. During a median follow-up of 58 (interquartile range, 43–73) months after the last ablation procedure, 97 of 150 (64.7%) patients remained in sinus rhythm without antiarrhythmic drugs. Another 14 (9.3%) patients maintained sinus rhythm after reinitiation of antiarrhythmic drugs, and an additional 15 (10.0%) patients regressed to paroxysmal recurrences only. Failure to terminate AF during the index procedure (hazard ratio 3.831; 95% confidence interval, 2.070–7.143; P <0.001), left atrial diameter ≥50 mm (hazard ratio 2.083; 95% confidence interval, 1.078–4.016; P =0.03), continuous AF duration ≥18 months (hazard ratio 1.984; 95% confidence interval, 1.024–3.846; P <0.04), and structural heart disease (hazard ratio 1.874; 95% confidence interval, 1.037–3.388; P =0.04) predicted arrhythmia recurrence. Conclusions—: In patients with persistent AF, an ablation strategy aiming at AF termination is associated with freedom from arrhythmia recurrence in the majority of patients over a 5-year follow-up period. Procedural AF nontermination and specific baseline factors predict long-term outcome after ablation. Abstract : Supplemental Digital Content is available in the text.